Implementation of Information and Communication Technology (ICT) System in Archive Management at Priangan Muhammadiyah Elementary School in Bandung City - Suryadhiningrat, Raden Fitri Karina (Universitas Pendidikan Indonesia, 2023)
The rapid development of technology in the current digitalization era has a positive impact on the smoothness and ease of carrying out various activities of educational organizations, one of which is archiving. . By maximizing the use of Information and Communication Technology (ICT) systems in archival management, it will facilitate the process of finding the necessary data, documents or archives. One of the problems faced in some educational organizations is the management of archival documents that are still manual (looking one by one) and conventional. Because the storage is still simple (such as in boxes, or paper folders and placed in display cases that are not in accordance with archive storage security standards, these things are also a threat to archive documents because of the vulnerability of the storage place and will not protect the archive when exposed to dust or exposed to natural disasters. So training was given to teachers and administrative staff (TU), especially at Priangan Muhammadiyah Elementary School in Bandung City. By using a qualitative research method with a descriptive approach, meaning that the author goes directly to the field. To collect valid and objective data, the author uses data collection techniques by means of observation, interviews (interviews) and documentation. The solution found is that with the existence of ICT-based archival management with the digitization of document archives, search capabilities and file sections can be easily found and retrieved for reuse. Data viewing can also be used as a backup plan in the event of damage to files or archive documents so that they can be restored. Therefore, this activity is expected to help manage ICT-based archive management for schools to improve time efficiency and limited human resources.